Curriculum of Love as Epistemology of Character Education in the Society 5.0 Era - Shodikin, Eko Ngabdul; Saputro, Budiyono; Miftahuddin, Miftahuddin; Marsita, Azizah Tri; Maftuch, Fais (FONDATIA, 2025)
The moral crisis in primary education—marked by declining empathy, increased student conflict, and the dominance of academic achievement—necessitates curriculum innovation grounded in affective values. This study aims to describe the implementation of the Kurikulum Cinta (Curriculum of Love) as a character-strengthening model at SDIT Cahaya Hati Pedan, focusing on teachers’ understanding, implementation strategies, encountered challenges, and its impact on student behavior. Employing a qualitative case study design, the research involved five teachers as participants through semi-structured interviews, observation, and analysis of instructional documents. Data were analyzed using the Miles and Huberman model, involving systematic stages of data reduction, display, and verification. The findings indicate that all teachers understand the Kurikulum Cinta as a humanistic approach emphasizing compassion, empathy, and respect for students. Implementation strategies include affective, non-punitive methods such as advice, rewards, positive touch, and motivation. Major challenges stem from internal student factors (60%), such as low learning motivation and social conflict, and external factors (40%), including teacher limitations, parenting styles, and gadget dependency. Nevertheless, 80% of teachers reported positive behavioral changes among students, including increased empathy, harmony, care, and enthusiasm for learning, while 20% observed gradual shifts toward responsible behavior. These findings suggest that the Kurikulum Cinta is effective in enhancing character education, although its success requires the support of a cohesive ecosystem involving families, schools, and aligned digital policies.